Evidence By Testimony In Case Of Flagrante Delicto - سبقجي, خالد; صفاء أوتاني , (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The current research aims to familiarize the reader with the conditions of testimony and the procedures for hearing it in the case of a flagrant offense and the extent of its evidentiary strength, given the importance of this offense, as the legislator granted the authorities investigating this offense exceptional investigative powers, with the aim of collecting evidence before the hand of tampering extends to it, and before The current research aims to familiarize the reader with the conditions of testimony and the procedures for hearing it in the case of a flagrant offense and the extent of its evidentiary strength, given the importance of this offense, as the legislator granted the authorities investigating this offense exceptional investigative powers, with the aim of collecting evidence before the hand of tampering extends to it, and before يهدف البحث الحالي إلى تعريف القارئ بشروط الإدلاء بالشهادة وإجراءات سماعها في حالة الجرم المشهود ومدى قوتها الاستدلالية ، لأهمية هذه الجريمة ، حيث أعطى المشرع للجهات التي تحقق في هذه المخالفة. صلاحيات تحقيقية استثنائية بهدف جمع الأدلة قبل أن تمتد يد العبث إليها وقبل ذلك The current research aims to acquaint the reader with the conditions of testimony and the procedures for hearing it in the case of a flagrant offense and the extent of its evidentiary strength, given the importance of this offense, as the legislator granted the authorities investigating this offense exceptional investigative powers, with the aim of collecting evidence before the hand of tampering reaches it, and before يهدف البحث الحالي إلى تعريف القارئ بشروط الإدلاء بالشهادة وإجراءات سماعها في حالة الجرم المشهود ومدى قوتها الاستدلالية ، لأهمية هذه الجريمة ، حيث أعطى المشرع للجهات التي تحقق في هذه المخالفة. صلاحيات تحقيقية استثنائية بهدف جمع الأدلة قبل أن تصل إليها يد العبث وقبل ذلك Can't load full results Try again Retrying... Retrying... Over time, it weakens the features of the facts on which it is focused. As for the research methodology, I relied in my research on the descriptive analytical approach in my presentation of the research ideas and points, where the research was divided into two sections. In the first research, I addressed the definition of the offence and what comes down to its status, as well as the objective and formal rules required in the witness and testimony, and the procedures for hearing it by the forensic investigator under the penalty of wasting it as evidence, and addressed in the second research the evidentiary force of the testimony heard during the investigation of the offence, relying on what was settled by the jurisprudence of the Syrian Court of Cassation in matters and points that were subject to jurisprudential and judicial dispute, with the aim of understanding the various aspects of the research, and taking an in-depth look on the subject of the research. The research concluded with a number of conclusions and suggestions that it reached through researching a number of points that the penal legislator was silent about. I conducted my research in the city of Lattakia during the period between August 2021 and January 2022.